Resolving land disputes in East Asia : exploring the limits of law / edited by Hualing Fu and John Gillespie. - Fu, Hualing; Gillespie, John (John Stanley) (Cambridge University Press, 2014)
Economic development and mass urbanization have unleashed unprecedented levels of land disputes in East Asia. In China and Vietnam especially, courts and other legal institutions struggle to find lasting solutions. It is against this background of legal failure that this book brings together leading scholars to understand how state agencies, land users and land developers imaginatively engage with each other to resolve disputes. Drawing on empirically rich case studies, contributors explore the limits of law and legal institutions in resolving land disputes and reveal insights into how key actors in East Asia understand land disputes. Their studies reveal promising dispute resolution practices and point to the likely ways that states will deal with land disputes in the future.